ANALYSIS FEASIBILITY AQUACULTURE BUSINESS OF KERAPU CANTIK (Epinephelussp.) IN FLOATTING NET CAGES AT POKDAKAN HARAPAN BARU SUNGAI NIPAH VILLAGE NAGARI IV JURAI, PAINAN SELATAN SUB-DISTRICT, PESISIR SELATAN REGENCY WEST OF SUMATERA BARAT - Farah Aisyah; Lamun Bathara; Darwis AN (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbtraksThis research was aimed to knowthe total investment, income and profit and then to analyze feasibility aquaculture business of Kerapu Cantik (Epinephelus sp.) in KJA at pokdakan Harapan Baru. This research has been done in 11 February until 22 February 2019. The method used within this research was survey method. There is5 respondents used , they are members of grup pokdakan Harapan Baru who be responsibility people an his own manage floatting net cages. Result of the research showed that the unit KJA 8 net bag have total investme of an average IDR 225.835.000,-,income of an average IDR 71.662.500,- and profit of an average IDR 13.075.000,- per year. And then the unit KJA 10 net bag had total investment of an average IDR 264.101.667,-, income of an average IDR 68.580.000,- and profit of an average IDR 10.125.833,- per year. Analysisfeasibility aquaculture business unit KJA 8 net bag had RCR average value1,21, FRR 5,77% and PPC 10,75 period. And then unit KJA 10 net bag had average value RCR 1,16, FRR 3,81 % and PPC 13,57 period.Keywords: Total Investment, Income, Pofit, Household, AnalysisFeasibility Aquaculture Business, Pokdakan Harapan Baru